2021
DOI: 10.21273/hortsci16186-21
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Resistance of Lactuca spp. against Fusarium oxysporum f. sp. lactucae Race 1

Abstract: Fusarium wilt of lettuce is caused by the pathogen Fusarium oxysporum f. sp. lactucae (Fol) and is a growing threat to global lettuce production. Fol was first detected in Florida in 2017 and was subsequently confirmed as race 1. Management strategies for this long-persisting soil pathogen are limited, time-consuming and expensive, and they may lack efficacy. Identifying diverse sources of genetic resistance is imperative for breeding adapted cultivars with durable resistance. The objectives of this study were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Disease severity seems to be related to the cultivar characteristics, to isolate aggressiveness, and to inoculation conditions for the same race of inoculum virulence and density (Garibaldi et al, 2004b;Scott et al, 2010b;Gilardi et al, 2021;Cabral and Reis, 2013;Cabral et al, 2019;Murray et al, 2021). Inconsistency between disease development and the susceptibility of the cultivars for trials carried out in different periods (Oct, Nov, Dec) or temperature ranges was observed by Cabral et al (2014).…”
Section: Discussionmentioning
confidence: 95%
“…Disease severity seems to be related to the cultivar characteristics, to isolate aggressiveness, and to inoculation conditions for the same race of inoculum virulence and density (Garibaldi et al, 2004b;Scott et al, 2010b;Gilardi et al, 2021;Cabral and Reis, 2013;Cabral et al, 2019;Murray et al, 2021). Inconsistency between disease development and the susceptibility of the cultivars for trials carried out in different periods (Oct, Nov, Dec) or temperature ranges was observed by Cabral et al (2014).…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, there are also specific PCR assays published for both Fola1 (Pasquali et al, 2007) and Fola4 (Gilardi et al, 2017b). Although resistance to Fola1 is available within commercial cultivars (Garibaldi et al, 2004; Scott et al, 2010; Murray et al, 2021), these are not always adapted or suitable for some locations and are often also susceptible to Fola4. Moreover, the lettuce cultivars commonly used in indoor production in Europe are highly susceptible to Fola4 and hence the plant breeding industry has had to try and react quickly to identify and deploy resistant cultivars to this new race.…”
Section: Introductionmentioning
confidence: 99%